The role of theories in social marketing in predicting physical activity behavior among the youth. Issue 4 (14th October 2019) - Tweneboah-Koduah, Ernest Yaw; Adams, Matilda; Acheampong, George
Abstract : Purpose: The purpose of this paper is to integrate the theory of planned behavior (TBP) and the technology acceptance model (TAM) in social marketing to predict and explain technology adoption (gym equipment use) in physical activity (PA) behavior among Ghanaian youth. Design/methodology/approach: A quantitative approach was adopted for this study. The empirical data for this paper were drawn from 314 youth who are gym equipment users. The hypothesized relationships were analyzed using structural equation modeling. Findings: This study found that the salient beliefs, namely, attitude, subjective norm and behavioral control toward gym equipment use, do not sufficiently explain PA adoption. However, a better result emerges when these salient beliefs are combined with perceived usefulness (PU) and ease of use (TAM). Practical implications: This paper provides evidence for issues of potential research, policy and managerial interest. The study findings showed that PA adoption, not PEOU, was directly impacted by PU. Thus, policymakers and implementers of social marketing intervention programs should promote the positive attitude toward gym equipment technology use and the perceptions of usefulness (improve cardiorespiratory fitness, feeling healthy and building muscle strength) of using gym equipment technology instead of ease of use to increase PA technology adoption behavior. Originality/value: Considering the uniqueness of this current study in the Ghanaian context, to the best of the authors' knowledge, this paper is the first to integrate two influential theories, namely, the TPB and TAM, to examine the effects of the TPB and TAM variables on the adoption of technology (gym equipment use) in PA among the youth.